2013
DOI: 10.2147/oaem.s43070
|View full text |Cite
|
Sign up to set email alerts
|

End-tidal arterial CO2 partial pressure gradient in patients with severe hypercapnia undergoing noninvasive ventilation

Abstract: Background:Patients with severe hypercapnia represent a particularly serious condition in an emergency department (ED), requiring immediate attention. Noninvasive ventilation (NIV) is an integral part of the treatment for acute respiratory failure. The present study aimed to validate the measurement of end-tidal CO 2 (EtCO 2 ) as a noninvasive technique to evaluate the effectiveness of NIV in acute hypercapnic respiratory failure. Methods: Twenty consecutive patients admitted to the ED with severe dyspnea were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In healthy anaesthetised patients, the monitoring of end-tidal CO 2 pressure (PetCO 2 ) is mandatory even if it underestimates the PaCO 2 , with a gradient around 4.5–13 mm Hg [ 2 ]. Lung diseases are associated with pulmonary heterogeneity, and the PaCO 2 –PetCO 2 gradient rises in unpredictable proportions [ 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, the PetCO 2 value cannot be taken as a good estimate of alveolar PCO 2 and hence cannot be used as an estimate of PaCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In healthy anaesthetised patients, the monitoring of end-tidal CO 2 pressure (PetCO 2 ) is mandatory even if it underestimates the PaCO 2 , with a gradient around 4.5–13 mm Hg [ 2 ]. Lung diseases are associated with pulmonary heterogeneity, and the PaCO 2 –PetCO 2 gradient rises in unpredictable proportions [ 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, the PetCO 2 value cannot be taken as a good estimate of alveolar PCO 2 and hence cannot be used as an estimate of PaCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the association between EtCO2 and PaCO2 has been established, but the accuracy of this method is still debated. [4][5][6][7] In a study comparing the relationship between EtCO2 and PaCO2 in the prone and supine positions, it was found that under normal circumstances, EtCO2 is a useful tool for monitoring PaCO2, but its accuracy may decrease when using different surgical techniques and in different positions. 8 Overall, measuring and monitoring EtCO2 is an important aspect of critical patient care.…”
Section: Introductionmentioning
confidence: 99%